Dynamic measurement via laser interferometry : crystal growth monitoring and modal parameter analysis - Yang, Chong (2018)
Generally there are two categories of noncontact laser interferometric methods commonly used in dynamic measurement, camera-based full-field interferometry and photo-sensor-based laser Doppler interferometry. The two methods have different advantages and disadvantages thus are suitable for different applications. The camera-based interferometry enjoys the valuable merit of full-field observation and measurement. In this paper, one typical full-field interferometry, digital holography, is employed to monitor the growth process of aqueous sodium chlorate crystals. The phase proportional to the solution concentration is retrieved from the holograms captured by CCD camera in real time. There exist no phase ambiguity problem in holography compared with other optical interferometric methods. On the other hand, laser Doppler interferometry is usually a point-wise measurement but with a very high temporal sampling rate. A multipoint laser Doppler interferometer is proposed for modal parameter measurement in this paper. The multiple transient vibration signals of spatially separated points on a beam structure subjected to a shock excitation are recorded synchronously. The natural frequencies and mode shapes are extracted in the signal processing stage. This paper shows that laser interferometry is able to contribute more to the practical applications in dynamic measurement related fields.